2002
DOI: 10.1029/2001ja000198
|View full text |Cite
|
Sign up to set email alerts
|

Observations of two types of Pc 1–2 pulsations in the outer dayside magnetosphere

Abstract: [1] Analysis of high time resolution magnetometer data from the Polar satellite and from an array of high-latitude ground stations in Antarctica has identified 20 simultaneously observed Pc 1-2 wave events in the outer dayside magnetosphere during the first 17 months of Polar operations. In contrast to most earlier satellite studies of Pc 1-2 waves, based on data from equatorial satellites near apogee which moved only slowly across L shells if at all, the initial orbit of Polar allowed it to rapidly cross oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
120
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 46 publications
7
120
2
Order By: Relevance
“…Our data would be consistent with those of Anderson and Hamilton if such compressions occur about 10% of the time. On the other hand, our fraction of compression related events seems to be significantly less than that found by Engebretson et al (2002).…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Our data would be consistent with those of Anderson and Hamilton if such compressions occur about 10% of the time. On the other hand, our fraction of compression related events seems to be significantly less than that found by Engebretson et al (2002).…”
Section: Discussioncontrasting
confidence: 44%
“…This model explains the higher occurrence rates of Pc1 waves at large L by Anderson et al (1992a) (up to the maximum L-value sampled by AMPTE/CCE), because compressions have a larger effect on the region close to the magnetopause than on the inner magnetosphere. Engebretson et al (2002) examined the set of Pc 1 events observed simultaneously by an array of ground stations in Antarctica and by the Polar spacecraft during the first 18 months of satellite operation. They found that 75% of these events occurred at the same time as magnetospheric compressions, although about half of these events are associated with spatially localized distribution functions (apparently another cause of EMIC waves).…”
Section: Introductionmentioning
confidence: 99%
“…Olsson et al [2004] also noted that the ion shell distributions observed on Polar consisted almost exclusively of H + ions. Ion shell distributions with dual loss cones were also noted by Engebretson et al [2002] in Polar satellite data association with electromagnetic ion cyclotron (EMIC) waves observed during very quiet times in the outer dayside magnetosphere.…”
Section: Introductionmentioning
confidence: 98%
“…Engebretson et al (2002) studied Pc1-2 events recorded simultaneously on the ground by the Antarctic meridional magnetometer chain located from the auroral ( = −66.5…”
Section: N Yagova Et Al: Mm100 Champ and Themis Observationsmentioning
confidence: 99%
“…• ) geomagnetic latitudes and are attributed to cusp and auroral regions (Bering III et al, 1998;Engebretson et al, 2002). Bering III et al (1998) mentioned ≈ 160 mHz emissions in the geomagnetic field at South Pole station ( = −74…”
Section: N Yagova Et Al: Mm100 Champ and Themis Observationsmentioning
confidence: 99%